Pesan Moral Dari Film Miracle In Cell No 7 Versi Indonesia : Analisis Semiotika - Khaerani, Lydia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Films are not only a medium of entertainment, but also a means of conveying strong moral messages to society. The Indonesian version of the film Miracle in Cell No. 7 tells an emotional story about the love between a father and son and the legal injustice that occurs. This study aims to reveal the moral message in the film through a semiotic analysis approach. The method used is descriptive qualitative with Roland Barthes’ semiotic theory as the main analytical tool. The results of the study show that this film conveys various moral messages such as the importance of family affection, honesty, social solidarity, and criticism of the legal system that does not side with the vulnerable. This finding confirms that films can be a social reflection that is full of human values.